Pengaruh Return On Asset (ROA) Terhadap Harga Saham Pada Perusahaan Retail Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Lia Lestari, Helma; Nugraha Irawan S, Rama; Kurniadi, Yudi (EKOBIMA, 2025)
This study aims to determine and analyze the effect of Return On Assets on stock prices in Retail Companies Listed on the Indonesia Stock Exchange for the 2018 - 2020 period. The population in this research is a company engaged in retail that are listed on the Indonesia Stock Exchange for the 2018-2020 period. The sample in this study was taken using purposive sampling method. A total of 30 company annual reports have been analyzed using simple linear regression analysis. The results showed that Return On Assets had an effect on stock prices.